(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
The most important consideration in designing protocols for wireless sensor networks is the energy constraint of nodes because in most cases battery recharging is inconvenient or impossible. Therefore, many researches have been done to overcome this demerit. Clustering is one of the main approaches in designing scalable and energy-efficient protocols for wireless sensor networks. The cluster heads take the task of data aggregation and data routing to decrease the amount of communication and this prolongs the network lifetime. LEACH protocol is one of the famous of them. In this paper, we proposed a novel scheme to investigate the cluster, the Fuzzy Logic Cluster Leach Protocol (FUZZY-LEACH), which uses Fuzzy Logic Inference System (FIS) in the cluster process. We demonstrate that using multiple parameters in cluster reduces energy consumption. We compare our technique with the LEACH protocol to show that using a multi parameter FIS enhances the network lifetime significantly. Simulation results demonstrate that the network lifetime achieved by the proposed method could be increased by nearly 28.5% more than that obtained by LEACH protocol in Â scenario, and by nearly 26.4% more than that LEACH protocol in Â scenario.